n-Alkanes for grazing studies with ruminants: where can we go? - Alloui M.N.; Keli A.; De Vega A. (Feeding and management strategies to improve livestock productivity, welfare and product quality under climate change, 2013)
An attempt was made to estimate the amount and quality of pasture consumed by sheep, using simultaneously faecal microhistology procedures and n-alkanes markers as markers. Cuticles of fieldsurveyed plants were characterized and n-alkane profiles of those consumed by the animals (cuticles found in faeces) determined to estimate diet composition and then dry matter intake and digestibility. Since in grazing conditions faecal recoveries of the different n-alkanes cannot be calculated directly, they were estimated by dosing through that of dotriacontane (C32), an artificial artificially dosed alkane and quantifying its recovery in . In the present work large differences were observed when diet composition was estimated using different methods of calculation. No method was able to detect all species identified by faecal microhistology, except in the case of six out of the 24 animals in which the composition of the diet was estimated. It can be concluded from the results that good estimates of diet composition and intake are obtained in grazing animals, using n-alkanes as markers, including only the discriminant hydrocarbons in the calculations. Also better results of diet composition (more compatible with microhistological findings in the faeces) and intake (more compatible with live weight changes of the grazing animals) are obtained applying faecal recovery to diet components instead to faeces. Besides, it seems necessary to estimate accurately the faecal recoveries of n-alkanes, even in grazing conditions, as they largely influence the digestibility results. Furthermore, it is important to use a large population of experimental animals as in our case only 20 % presented consistent results of diet composition and intake.
14. International Seminar of the Sub-Network on Nutrition of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Sheep and Goats, 2012/06/15-17, Hammamet (Tunisia)